Who Creates Jobs? - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2012)
There is a consensus that jobs are vital in translating economic growth into lasting poverty reduction and social cohesion. But who creates jobs is an understudied field. This economic premise argues that there is a strong link between initial levels of young and small firms and subsequent job growth, as evidenced in India. The economic geography of entrepreneurship in India is still evolving. It is worrying that there are too few entrepreneurs in India for its stage of development. Yet there is no question that entrepreneurship works cities and states that have embraced entrepreneurship have created more jobs. However, the link between entrepreneurship and job growth is not automatic. Cities that have a higher quality of physical infrastructure and a more educated workforce attract many more entrepreneurs. Supportive incumbent industrial structures for input and output markets are strongly linked to higher entrepreneurship rates. There are many policy levers that can be used by policy makers to promote entrepreneurial growth. Instead of being preoccupied with firm chasing attracting large mature firms from other locations policy makers should focus on encouraging entrepreneurship in their communities.